2018
DOI: 10.1213/ane.0000000000002301
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index Measurements Are Not Degraded During Aeromedical Evacuations

Abstract: For a decade, depth of anesthesia monitoring has become a reality in the operating room. It provides valuable help for managing anesthesia, especially for unstable patients. This might be particularly relevant during aeromedical evacuation. In this study, we aimed to assess the validity of the bispectral index (BIS) during long-range patient transportation aboard fixed-wing aircraft. BIS was recorded in 30 patients, 25 under anesthesia and 5 awake, during aeromedical evacuations performed by the French Air For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The BIS was used to judge the level of sedation and monitor the depth of anesthesia. The BIS value ranges from 0 to 100: 85 to 100 for normal state, 65 to 85 for sedative state, and 40 to 65 for anesthetic state . The OAA/S score ranges from 1 to 5: 1 = does not respond to mild prodding or shaking; 2 = responds only after mild prodding or shaking; 3 = responds only after name is called loudly and/or repeatedly; 4 = lethargic; and 5 = responds to name spoken in normal tone.…”
Section: Methodsmentioning
confidence: 99%
“…The BIS was used to judge the level of sedation and monitor the depth of anesthesia. The BIS value ranges from 0 to 100: 85 to 100 for normal state, 65 to 85 for sedative state, and 40 to 65 for anesthetic state . The OAA/S score ranges from 1 to 5: 1 = does not respond to mild prodding or shaking; 2 = responds only after mild prodding or shaking; 3 = responds only after name is called loudly and/or repeatedly; 4 = lethargic; and 5 = responds to name spoken in normal tone.…”
Section: Methodsmentioning
confidence: 99%
“…Whether there is awareness, memory, and implicit memory in anesthesia depends on the sedation depth in anesthesia. It is found that the BIS value is 75∼90 in light sleep, 75∼92 in rapid eye movement, and 20∼70 in slow-wave sleep [ 18 ]. It is more advantageous to distinguish the existence and disappearance of consciousness.…”
Section: Related Workmentioning
confidence: 99%